(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Recurrent bronchitis is one of the most common respiratory disorders in childhood and represents a significant challenge in pediatric healthcare due to its high incidence and the risk of progression to chronic respiratory diseases. Frequent episodes of bronchial inflammation can negatively affect the physical development and overall health status of children. Early detection of clinical manifestations and accurate diagnostic assessment play an essential role in preventing complications and improving treatment outcomes. The aim of this study is to investigate the clinical and diagnostic features of recurrent bronchitis in children and to analyze approaches for optimizing therapeutic and preventive measures. The research focuses on identifying major clinical symptoms, evaluating diagnostic criteria, and determining risk factors that contribute to repeated episodes of bronchial inflammation in pediatric patients. Particular attention is given to the role of modern diagnostic methods, including clinical examination, laboratory analysis, and instrumental assessment, in improving the accuracy of diagnosis. In addition, the study evaluates therapeutic strategies used in the management of recurrent bronchitis and proposes optimized preventive approaches aimed at reducing the frequency of disease recurrence. These strategies include timely medical intervention, strengthening of the immune system, environmental risk reduction, and implementation of preventive healthcare programs. The results of this research highlight the importance of a comprehensive diagnostic approach and individualized treatment strategies for children with recurrent bronchitis. Optimization of therapeutic and preventive measures can significantly decrease recurrence rates, improve respiratory function, and enhance the overall quality of life in pediatric patients.